Analysis of the Development of Augmented Reality Based Learning Media on High School Physics Material - Fadhiel, M. Al; Mufit, Fatni (Journal of Innovative Physics Teaching, 2024)
One of the purposes of using information and communication technology is to increase the efficiency and effectiveness of learning. One technology that can be used is augmented reality (AR) technology. One innovation that can be developed is the development of AR-based learning media. This research discusses the effectiveness of developing Augmented Reality (AR)-based learning media in an effort to increase students' understanding of high school physics material. To measure the level of effectiveness, it is seen from the results of the Validation Test from material experts, media experts, as well as responses from surveys conducted among practitioners. This research is due to students' low understanding in studying physics material which is very difficult to imagine or understand because the concepts are abstract. Therefore, there is a need for innovative learning media so that abstract physics concepts can be explained by visualizing them using Augmented Reality (AR). The research method used was a quantitative approach and literature study as a data collection method. This research took 10 references related to research objectives published from 2017 to 2023. From the analysis carried out, it was found that the use of Augmented Reality (AR) in physics learning can improve students' understanding abilities in physics learning.